Siyāsah Dauliyah and the Global Crisis: A Fiqh Siyasah Perspective on the U.S.–Israel–Iran Conflict and Indonesia’s Strategic Role in Peace Diplomacy - Jumat, Gani; Baso Malla, Hamlan Andi; Ahmadan, Ahmadan; Mera, Nasaruddin; M. Said, Idrus (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Geopolitical tensions between the United States, Israel, and Iran have developed into one of the most dangerous hotspots in today's world political constellation. This reality confirms that the dynamics of contemporary warfare have transcended traditional geographic boundaries and demand a response that blends diplomatic dimensions with deep ethical considerations. In the midst of such complexity, the tradition of Islamic political thought offers a relevant perspective through the concept of siyāsah dauliyah a normative framework in fiqh siyasah that governs the relationship between nations. This concept lays the foundation for the values of justice, recognition of the sovereignty of other states, loyalty to the pacts and agreements concluded, as well as strict restrictions on the use of armed violence. This study intends to examine the trilateral conflict using the lens of siyāsah dauliyah as the main analytical lens. Methodologically, this study relies on a qualitative approach by combining literature studies and normative studies on the treasures of Islamic political jurisprudence, combined with the latest international relations literature. The findings reveal that the spirit of siyāsah dauliyah actually puts forward the peaceful path - through negotiations, open communication, and multilateral cooperation as the main mechanism for resolving disputes between countries, not through armed confrontation. Interestingly, this orientation has a strong resonance with Indonesia's foreign policy doctrine known as the "bebas aktif" principle."Indonesia's commitment to continuously promote the alleviation of tensions and peaceful settlement of international disputes reflects similar values. Furthermore, Indonesia's willingness to take on the role of a dialogue facilitator or potential mediator in the US–Israel–Iran conflict shows the country's seriousness in realizing global peace. Thus, the integration of ethical principles from the Siyasah Fiqh tradition into contemporary diplomatic practice has the potential to strengthen Indonesia's capacity as a significant actor in conflict resolution and international peacebuilding efforts.